ECG and NIBP Simulator in One Device Display on TFT Nextion - Melinda, Cantika; Wisana, I Dewa Gede Hari; Pudji, Andjar; Triwiyanto, Triwiyanto (Indonesian Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2023)
Accurate monitoring of NIBP (Non-Invasive Blood Pressure) parameters using vital sign monitors is crucial for patient care. Therefore, calibration of vital sign monitors is essential to ensure their safety and reliability. A vital sign simulator was developed in this study, integrating ECG and NIBP parameters with a TFT Nextion display. The aim is to calibrate ECG and NIBP readings on vital sign monitors. The system utilized the Arduino Mega 2560 as the central controller and the MPX5050GP sensor for NIBP measurement and motor pump control. The NIBP parameters were measured at two settings: 60/30 and 80/50. The results showed a maximum systolic error of 3.5% and a diastolic error of 5.6% for the NIBP setting of 80/50. The largest standard deviation value of 2.05 was observed at the NIBP setting of 60/30. The highest uncertainty value of 0.5 was also found in the NIBP 60/30 setting. The obtained data indicated stable module readings within the acceptable threshold for vital sign monitor calibration. The developed vital sign simulator offers a reliable means of calibrating NIBP parameters, enabling accurate blood pressure measurements. Further research and refinement can be conducted to enhance the system's precision and expand its capabilities for calibration of additional vital sign parameters. By ensuring accurate calibration, healthcare professionals can rely on vital sign monitors for effective patient monitoring and diagnosis.